2010
DOI: 10.1175/2009wcas1013.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ice Storm Impacts over Time: 1886–2000

Abstract: Ice storms have a variety of negative effects on society. Through an analysis of newspaper accounts of nine exceptional ice storms, the most widespread and longest lasting impact is the loss of electrical power. Power outages also cause secondary effects, such as carbon monoxide poisoning and fire, and they can force people to leave their homes because of a lack of heat. Other impacts of ice storms are transportation disruptions, school and business closings, and economic losses to agriculture and some busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…While several studies of the human impacts of wintery precipitation have taken sectoral approaches -e.g., impacts on utilities (Call, 2010) or transportation (Andrey, Mills, Leahy, & Suggett, 2003;Call, 2010) -Changnon's approach was generally less sector-specific, focusing instead on the spatial and temporal distribution of adjusted insured losses caused by freezing rain, sleet, and snow. His studies found that these losses have been centered in the eastern United States (Changnon, 2007(Changnon, , 2009b, with large storms producing much of the damage (Changnon, 2003b(Changnon, , 2008dChangnon & Changnon, 2007).…”
Section: Wintery Precipitationmentioning
confidence: 99%
“…While several studies of the human impacts of wintery precipitation have taken sectoral approaches -e.g., impacts on utilities (Call, 2010) or transportation (Andrey, Mills, Leahy, & Suggett, 2003;Call, 2010) -Changnon's approach was generally less sector-specific, focusing instead on the spatial and temporal distribution of adjusted insured losses caused by freezing rain, sleet, and snow. His studies found that these losses have been centered in the eastern United States (Changnon, 2007(Changnon, , 2009b, with large storms producing much of the damage (Changnon, 2003b(Changnon, , 2008dChangnon & Changnon, 2007).…”
Section: Wintery Precipitationmentioning
confidence: 99%
“…The accumulated amounts of precipitation and resulting ice coatings in freezing rain events are generally modest, and they mostly impact only traffic due to reduced friction (Schepers et al, ). However, larger loads of accreted ice also occasionally occur, and these events cause substantial damage to trees and power grids (Call, ; Nagel et al, ) and pose a threat to other critical infrastructure (Helander, ). Strong winds can increase the resulting damages either during or after the freezing rain (Call, ; Degelia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, larger loads of accreted ice also occasionally occur, and these events cause substantial damage to trees and power grids (Call, ; Nagel et al, ) and pose a threat to other critical infrastructure (Helander, ). Strong winds can increase the resulting damages either during or after the freezing rain (Call, ; Degelia et al, ). The impacts differ depending not only on the accumulated precipitation amounts but also on the duration of the freezing rain events.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, heavy snowfall or ice storms significantly disrupt orderly transportation on the ground and in the air, impair the ability of utility companies to supply electric power to businesses and homes, and raise concerns for public safety in general (Dore 2003;Roebber and Gyakum 2003;Ralph et al 2005;Bouilloud et al 2009;Call 2010;Cools et al 2010;Cerruti and Decker 2011;Ressler et al 2012;Grout et al 2012). In particular, heavy snowfall or ice storms significantly disrupt orderly transportation on the ground and in the air, impair the ability of utility companies to supply electric power to businesses and homes, and raise concerns for public safety in general (Dore 2003;Roebber and Gyakum 2003;Ralph et al 2005;Bouilloud et al 2009;Call 2010;Cools et al 2010;Cerruti and Decker 2011;Ressler et al 2012;Grout et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cold-season precipitation has been the focus of numerous numerical weather prediction (NWP) modeling studies in the past such as the evaluation of quantitative precipitation forecasts, rain-snow boundaries, or the timing of precipitation onset related to a synoptic storm and subsequent storm evolution (e.g., Garvert et al 2005;Grubi si c et al 2005;Ralph et al 2005 and2010;Mailhot et al 2010;Schuur et al 2012). Only a few investigations have been concerned with the skill of NWP models to accurately forecast the type of precipitation (e.g., Bocchieri and Maglaras 1983;Czys et al 1996;Hux et al 2001;Cortinas et al 2002;Wandishin et al 2005).…”
Section: Introductionmentioning
confidence: 99%